Inhibition in the Dynamics of Selective Attention: An Integrative Model for Negative Priming - Schrobsdorff, Hecke; Ihrke, Matthias; Behrendt, Jörg; Hasselhorn, Marcus; Herrmann, J M. (Frontiers in Psychology, 2012)
We introduce a computational model of the negative priming (NP) effect that includes perception, memory, attention, decision making, and action. The model is designed to provide a coherent picture across competing theories of NP and to relate psychological experiments to physiological measurements. The model is formulated in terms of an abstract dynamics of activations of features, their binding into object entities or their semantic categorization as well as related memories and implied reactions. The dynamical variables interact in a connectionist network which is shown to be adaptable to a variety of experimental paradigms. We find that selective attention can be modeled by means of inhibitory processes and by a threshold dynamics. Considering the implementation it becomes obvious that the specificity of the experimental paradigm must be taken into account when predicting the nature of the NP effect.